Effectiveness of Hydrated Sodium Calcium Aluminosilicate (HSCAS) in Mitigating the Adverse Effects of Aflatoxin on In Vitro Rumen Fermentation of Wheat Straw - Singh, Ram; Saini, Ashwani Kumar; Dhial, Kritika; Pathak, Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
To study the effect of hydrated sodium calcium aluminosilicate (HSCAS) in ameliorating adverse effects of aflatoxin on in vitro rumen  fermentation, five treatment groups, viz., T1: control (wheat straw; 0.2 g); T2: T1+300 ppb Aflatoxin B1 (AFB1); T3: T2+0.33% HSCAS; T4:  T2+0.5% HSCAS and T5: T2+ 1.0% HSCAS were prepared and incubated in vitro. The results revealed that truly degradable dry matter  (TDDM), truly degradable organic matter (TDOM), gas production (GP), microbial biomass production (MBP) and partitioning factor (PF)  values in aflatoxin contaminated group (T2) were lower (p
Keywords: Aflatoxin; Buffalo; Hydrated sodium calcium aluminosilicate; In vitro Rumen fermentation